Supporting Children's Wellbeing Using the Reading Well Home Reading Program - O'Brien, Siobhan, (Critical New Literacies: The Praxis of English Language Teaching and Learning ;, 2025)
Discover the transformative power of The Reading WELL home reading program. This monograph unveils a groundbreaking approach to enhance child wellbeing through the use of developmental bibliotherapy. Parents and children engage in shared reading and discussions on the themes of body image, self-esteem, and resilience. Designed for children aged 8 to 10 years, this research not only fosters a love for reading but also provides a process to support emotional growth and learning. Backed by compelling theoretical insights, this book offers a profound insight to ways literature can act as a tool to promote eudemonic wellbeing and address issues of trauma in children's lives. Ideal for educators, psychologists, and parents, The Reading WELL sets a new standard in nurturing children's holistic development through the magic of storytelling.